Analisis Profitabilitas pada Perusahaan Manufaktur Go Publik yang Menerapkan Kebijakan Modal Kerja Agresif, Moderat, dan Konservatif di Bursa Efek Indonesia - Musdholifah Musdholifah; Eko Triambodo (Universitas Negeri Surabaya, 2018)
The companies profitability determined by the application of the right working capital policy. This research is to know the differences of profitability on the manufacturing company that using the agresive, moderate, and conservative working capital policy. The research sample are food and beverages industry then classified according 3 groups of working capital policy that was checked at 2004-2006. Quantitative method was used on this research which one-way ANOVA analysis was used to test different of profitability each company. The result indicated that the company with agresive working capital policy had lower profitability than company with moderate and conservative working capital policy this indicated contradiction with theory. The research conclusion there are not significant different between company whose applying agresive, moderate and conservative working capital policy also known that company adjusted of their applied working capital policy at period 2004-2006.